2010
DOI: 10.1021/om100688t
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State and Dynamic Solution Behavior of a Cationic, Two-Coordinate Gold(I) π-Allene Complex

Abstract: Summary: The cationic gold π-allene complex {[P(t-Bu) 2 obiphenyl ]Au[η 2 -H 2 CdCdC(CH 3 ) 2 ]} þ SbF 6 -was isolated in 98% yield from reaction of 3-methyl-1,2-butadiene with a mixture of [P(t-Bu) 2 o-biphenyl]AuCl and AgSbF 6 and was characterized by X-ray crystallography and variable-temperature NMR spectroscopy. These studies revealed preferential binding of gold to the less substituted CdC bond of the allene in both the solid state and solution and also revealed fluxional behavior consistent with π-face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…It is worth noting that the energy barrier for intermolecular 3-hexyne exchange with 6·SbF 6 is ! 6 kcal mol À1 lower than the energy barriers determined for the intermomolecular p-ligand exchange with [P- [9,12] This difference presumably reflects both the diminished steric environ- …”
Section: Effect Of Counterionmentioning
confidence: 78%
See 2 more Smart Citations
“…It is worth noting that the energy barrier for intermolecular 3-hexyne exchange with 6·SbF 6 is ! 6 kcal mol À1 lower than the energy barriers determined for the intermomolecular p-ligand exchange with [P- [9,12] This difference presumably reflects both the diminished steric environ- …”
Section: Effect Of Counterionmentioning
confidence: 78%
“…[6] Due to the central role of gold-p complexes in these mechanisms, there has been recent interest in the synthesis and study of cationic, two-coordinate gold-p complexes. [7] From these efforts, a number of mononuclear, cationic gold(I) complexes containing a p alkene, [8,9] alkyne, [10,11] allene, [12] conjugated diene, [13,14] or arene [15,16] p ligand and a sterically hindered, electron-rich supporting ligand, such as 1,3-bis- 3 , or PA C H T U N G T R E N N U N G (tBu) 2 -o-biphenyl, have been isolated and characterized both in the solid state and in solution. Conversely, mononuclear, cationic, two-coordinate goldp complexes containing a triphenylphosphine ligand have not been isolated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fürstneri solated ac omplex between tetradimethylaminoallene and Ph 3 PAuSbF 6 featuring h 1 central coordination [8] while Widenhoefer has also reported an X-ray crystal structure of the h 2 dimethylallene-Au + + PPh 3 complex. [9] Our objective wast ou se allenylphosphine oxides IV as probes for twot ypes of applications.T he first aim was the generation of new gold coordination complexes,p ossibly implying the phosphineo xide moiety. [10] These could be new precatalytic species or modelso fp roposedi ntermediates.T he second objective was to involve these substratesi nc ycloisomerization reactions when using appropriate Rs ubstituent on IV in order to deliver new phosphorus-containing chiral substrates.…”
mentioning
confidence: 99%
“…As expected, hydrogen bond acceptors with lower gold affinity (e.g., DMPU, DMF) [141][142][143][144][145][146][147][148] enhanced the rate of reaction (Scheme 14b), and ionic hydrogen bond acceptors (e.g., Bu4N Other research groups reported that certain compounds improved the chemical yields in selected gold catalyzed reactions. 153,154 One notable example is the …”
Section: Scheme 14 Additive Effects On Various Gold Catalyzed Reactisupporting
confidence: 63%